2015
DOI: 10.1021/acs.est.5b03405
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational Adaptation to Pollution Changes Energy Allocation in Populations of Nematodes

Abstract: Assessing the evolutionary responses of long-term exposed populations requires multigeneration ecotoxicity tests. However, the analysis of the data from these tests is not straightforward. Mechanistic models allow the in-depth analysis of the variation of physiological traits over many generations, by quantifying the trend of the physiological and toxicological parameters of the model. In the present study, a bioenergetic mechanistic model has been used to assess the evolution of two populations of the nematod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 52 publications
1
9
0
1
Order By: Relevance
“…Untangling an effect on maintenance cost or assimilation is, for example, particularly difficult when additional data on oxygen consumption are not available. Consequently, modeling work can fit equally well different MoA for a same contaminant, as observed for the effect of uranium on aquatic species (Augustine et al, 2012;Massarin et al, 2011;Goussen et al, 2015). In our study, the impact of BPA on v is the most suitable mode of action as it yields predictions particularly close to real values.…”
Section: Accepted Manuscript 43 Mode Of Action Of Imsupporting
confidence: 59%
“…Untangling an effect on maintenance cost or assimilation is, for example, particularly difficult when additional data on oxygen consumption are not available. Consequently, modeling work can fit equally well different MoA for a same contaminant, as observed for the effect of uranium on aquatic species (Augustine et al, 2012;Massarin et al, 2011;Goussen et al, 2015). In our study, the impact of BPA on v is the most suitable mode of action as it yields predictions particularly close to real values.…”
Section: Accepted Manuscript 43 Mode Of Action Of Imsupporting
confidence: 59%
“…Sixteen-generation studies on the effect of uranium to C. elegans found adaptation to exposure conditions for both exposed and control populations. Observed effects on fecundity were consistent between population treatments, whereas in one of the studies effects on body length showed differential evolution over the exposure duration once maternal effects diminished [15,16].…”
Section: Introductionmentioning
confidence: 78%
“…the environmental risk may in fact be much greater than estimated from short-term testing). Further, in C. elegans, mitigation of maternal effects was only found after at least four generations of exposure to uranium [16,17]. The result may be a failure of environmental protection by environmental quality standards derived from single generation toxicity tests in cases (such as for Ag ENPs and Ag ions) where multigenerational exposure is relevant, especially in those cases where standards are derived without use of assessment factors (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The organism level model needs to simulate life-history parameters such as survival, growth and reproduction because these determine population dynamics. As growth and reproduction are driven by an organisms’ energy balance, Dynamic Energy Budget models are particularly well suited to integrate toxicant and environmental stressors39404142.…”
Section: Integration Of Multiple Stressorsmentioning
confidence: 99%